PENGARUH PERPUTARAN MODAL KERJA DAN CURRENT RATIO TERHADAP RETURN ON ASSET PADA PT DHARMA SATYA NUSANTARA TBK. PERIODE 2014-2023 - Muhammad Zulfi Alfiansyah; Ria Rosalia Simangunsong (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine the effect of Working Capital Turnover and Current Ratio on Return On Assets at PT Dharma Satya Nusantara Tbk. Period 2014 until 2023. The research method used is a quantitative method with the type of quantitative associative research method. With secondary data obtained through financial reports obtained from PT Dharma Satya Nusantara Tbk. from the websites www.dharmasatyanusantara.com. This study uses multiple linear regression analysis, classical assumption test which includes normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, determination test (R Square), significant test includes statistical t test and F test. The results of this study are based on the results of the t test or partially (individually) for the Working Capital Turnover variable (X1) using SPSS 26 has a t-count value < t-table which is (0.418 < 2.365) with a significant level of 0.688 > 0.05 then Ho1 is accepted and Ha1 is rejected. Based on the results it can be concluded that Working Capital Turnover does not have a significant effect on Return On Asset. In the variable Current Ratio (X2) In the Current Ratio variable (X2) has a t-count value < t-table which is (1.548 < 2.365) with a significant level of 0.166> 0.05 then Ho2 is accepted and Ha2 is rejected. Based on the results it can be concluded that the Current Ratio partially does not significantly influence Return On Assets. Simultaneously Working Capital Turnover and Current Ratio have no significant effect on Return On Assets.